Out-of-plane effect on the sharp V-notch tip fields in power-law creeping solids: A three-dimensional asymptotic analysis. (1st February 2022) - Kong, Weichen; Dai, Yanwei; Liu, Yinghua
Abstract: Understanding the three-dimensional (3D) effect on the notch tip field is important for the fracture mechanics analysis of engineering materials and structures. This paper presents an asymptotic solution for 3D sharp V-notched structures subjected to mode Ⅰ creep loading condition. The asymptotic solution, including the singularities and stress field distribution functions, is obtained by introducing the out-of-plane constraint factor. It is found that the singular behavior is related to the notch angle, material creeping exponents, and the out-of-plane constraint factor. Specifically, singularity changes sharply near the free surface. K N t - T z solution is presented to describe the mode Ⅰ stress field around the tip of 3D V-notch under creep condition. Its accuracy and advantages compared with plane strain or plane stress solutions are validated by finite element analysis. The difference between effective ranges of K N t - T z solution and that of plane strain solution is clarified. Moreover, the effect of the creep time on the stress field is also shown. The solutions given in this paper could be beneficial for understanding the 3D effect on notch considering creep loading conditions.